Permanent cardiac pacing using anterior pectoral veins. Issue 3 (March 1980) - Arnold, A G
Abstract : We have used the anterior pectoral veins for inserting permanent transvenous cardiac pacemaker electrodes in 260 patients. Though this route is used in other centres it has not been published. We found it to be a reliable alternative to the more usual routes of pacemaker insertion, with a combined perforation and displacement rate of 9.6 per cent. We describe this technique of electrode insertion and compare the complication rates with those of other routes of implantation used in our department. All of the pacemaker implantations in this study were performed by doctors in the cardiology department, with no specialist surgical training.